SALMONELLA OSTEOMYELITIS OF RIBS - Khan, Imran; Mufti, Ahmad Jawad; Khan, Mah Muneer; Khan, Attaullah; Afridi, Humaira; Jan, Hizbullah (Journal of Ayub Medical College Abbottabad, 2018)
A 45-year-old diabetic male who was a farmer by profession, presented to Khyber Teaching Hospital with swelling and redness on the right side of the chest at the level of 8th rib for the past 5 months which was accompanied by fever and pain. He went to a local hospital where he was given broad spectrum antibiotics. He presented again with yellowish discharge from the wound. Dressing of the wound was done and he was referred to Khyber Teaching Hospital. On presentation, there was an open wound of about 4 cm on the right side of the chest wall at the level of 8th rib near the midclavicular line. X-ray revealed a lytic bone lesion near the costo-chondral junction of the 8th rib. CT scan also showed erosive changes at the above mention site. His fasting blood sugar was well above the normal range and his Alkaline Phosphatase was slightly raised. He was started on Insulin. Debridement and dressing were done and samples were taken for investigations. Bone tissue biopsy revealed inflammatory non-caseating tissue. Culture report was positive for Salmonella Typhi which was resistant to Ciprofloxacin. The patient was given antibiotic (co-amoxiclave) treatment to which he responded leading to a satisfactory recovery. Keywords: Osteomyelitis; Infection; Surgery, Ribs